2011
DOI: 10.1021/jf201953v
|View full text |Cite
|
Sign up to set email alerts
|

Use of Tetragenococcus halophilus as a Starter Culture for Flavor Improvement in Fish Sauce Fermentation

Abstract: The potential of Tetragenococcus halophilus as a starter culture for flavor improvement in fish sauce fermentation was elucidated. Four strains of T. halophilus isolated from fish sauce mashes were inoculated to anchovy mixed with 25% NaCl with an approximate cell count of 10(6) CFU/mL. The α-amino content of 6-month-old fish sauce samples inoculated with T. halophilus was 780-784 mM. The addition of T. halophilus MRC10-1-3 and T. halophilus MCD10-5-10 resulted in a reduction of histamine (P < 0.05). Fish sauc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
89
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(92 citation statements)
references
References 35 publications
2
89
1
Order By: Relevance
“…According to the Biolog identification, the reaction proated for lactic acid bacteria population by spread plate method using MRS agar containing 18% NaCl and 1.5% CaCO 3 and incubated at 30℃ for 5 days under anaerobic condition. The population of halotolerant bacteria was also monitored using modified JCM168 medium containing 20% NaCl and incubated at 37℃ for 5 days under aerobic condition (Udomsil et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the Biolog identification, the reaction proated for lactic acid bacteria population by spread plate method using MRS agar containing 18% NaCl and 1.5% CaCO 3 and incubated at 30℃ for 5 days under anaerobic condition. The population of halotolerant bacteria was also monitored using modified JCM168 medium containing 20% NaCl and incubated at 37℃ for 5 days under aerobic condition (Udomsil et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…5% (w/v) of cell suspension of T. halophilus was inoculated into initial Jiang Pei, and the physiochemical characteristics of Jiang Pei were monitored after ripening for 2 months. Microbiological analysis Jiang Pei sample (10 g) was aseptically taken at various fermented intervals and enumer- Rabie et al, 2011;Udomsil et al, 2011). Akolkar et al (2010) reported that exogenous addition of Halobacterium sp.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among halophilic lactic acid bacteria, Tetragenococcus are the most common in high-salt fermented food products. This bacterium has been found in various food products, such as salted anchovies [5], Japanese soya sauce [6], Japanese traditional fermented fish sauce (squid liver sauce) [7]. Recently, they have been isolated from Japanese-fermented puffer fish ovaries [8], Indonesian terasi shrimp paste [9], Cambodian fermented fish [10].…”
Section: Introductionmentioning
confidence: 99%